Crablet nursery of mud crab (Scylla paramamosain) with different feed types and stocking densities - Viet, Le Quoc; Hai, Tran Ngoc (Vietnam Journal of Marine Science and Technology, 2020)
This study aims to determine the appropriate feed type and stocking density to improve the survival rate and growth performance of mud crab crablet during the nursery stage. The study consisted of 2 experiments as follows: (1) Rearing crablets with different feed types (including commercial feed, artemia biomass and acetes biomass) and (2) rearing crablets at different stocking densities (including 100; 200; 300 and 400 inds/m2). All treatments were randomly set up in triplicate. The initial sizes of crablet were 3.24 ± 0.54 mm in length, 4.54 ± 0.79 mm in width and 0.018 ± 0.004 g in weight. The result showed that using acetes biomass gave the best results compared to other treatments. The survival rate was 58.8% and biomass was 118 inds/m2. The second experiment showed that rearing crablets at 100 inds/m2 reached the highest survival rate (90.7%) and biomass (91 inds/m2).